Induced osteogenesis using biodegradable and titanium periosteal distractors - Marwa Madi (Saudi Dental Journal)
Background: New bone formation can result from periosteal distraction. This is achieved through progressive uplifting of the periosteum by increasing the interface between it and the bone surface. Objective: This study investigated the impact of gradual periosteal distraction using biodegradable materials and titanium distraction devices. Materials and methods: 20 rabbits were separated into 2 groups. Distraction devices were placed in all groups after reflecting the calvarial periosteum. The device was actuated following 7 days. Group 1 got titanium device and Hydroxyapatite HA with poly-l-lactide (PLLA) device was utilized in group 2. Five animals were sacrificed from each group following 4 and 6 weeks. Newly formed bone was histologically and radiographically assessed. Results: The histological observations showed that both distraction devices successfully induced osteogenesis and effectively distracted the soft tissue following 4 and six weeks. The study showed scattered bone trabeculae, with adipose tissue and multiple dome-shaped bones. Micro-computed tomography showed newly formed bone that was far less radiopaque than the initial basal bone. The connective tissue appeared as a radiolucent area that decreased gradually toward the fixation point of the device. At 6 weeks, the percentage of new bone was significantly higher than at 4 weeks for both devices. The PLLA device showed more bone than did the titanium device at both 4 and 6 weeks, but no significant difference was observed. Conclusions: Both distraction devices were effective in distracting the periosteum and inducing new vascularized bone. The PLLA device induced more bone than the titanium device. Thus, the distractor composition may influence the new bone.